2022
DOI: 10.1111/mms.12980
|View full text |Cite
|
Sign up to set email alerts
|

Towards the definition of the humpback whale population units along the Mexican and Central American coasts in the Pacific Ocean

Abstract: The SPLASH project (2004)(2005)(2006) revealed complex population structure and migratory connections, but no regional effort was made along the southern Mexican Pacific coast until dedicated research was initiated in 2010. It is unclear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Despite the tremendous amount of data available for humpbacks in the North Pacific, delineating migratory herds remains challenging in many areas, particularly from the less-accessible feeding areas in Alaska and Russia. Even for the Central America wintering aggregation, which is composed of a single herd, stratifying by geography is problematic because data collected since the SPLASH study suggest that the Central America wintering aggregation extends into southern Mexico (Martínez-Loustalot et al, 2022), and may overlap in range with the herds that winter along the coast of northern Mexico (Ortega-Ortiz et al, 2022;Taylor et al, 2021). The situation is even more challenging in other wintering aggregations, where not only are there individuals from multiple feeding areas, but a growing body of data challenging our understanding of geographic structure within and possible connections between wintering grounds (Darling et al, 2019b;Derville et al, 2020;Garrigue et al, 2015;Lammers et al, 2023).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Despite the tremendous amount of data available for humpbacks in the North Pacific, delineating migratory herds remains challenging in many areas, particularly from the less-accessible feeding areas in Alaska and Russia. Even for the Central America wintering aggregation, which is composed of a single herd, stratifying by geography is problematic because data collected since the SPLASH study suggest that the Central America wintering aggregation extends into southern Mexico (Martínez-Loustalot et al, 2022), and may overlap in range with the herds that winter along the coast of northern Mexico (Ortega-Ortiz et al, 2022;Taylor et al, 2021). The situation is even more challenging in other wintering aggregations, where not only are there individuals from multiple feeding areas, but a growing body of data challenging our understanding of geographic structure within and possible connections between wintering grounds (Darling et al, 2019b;Derville et al, 2020;Garrigue et al, 2015;Lammers et al, 2023).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Numerous studies have aimed to improve our understanding of the population structure of humpback whales in their wintering areas in the North Pacific (Baker et al, 1993(Baker et al, , 1994(Baker et al, , 2013Barlow et al, 2011;Bettridge et al, 2015;Calambokidis et al, 2001;González-Peral, 2011;Martien et al, 2020;Martínez-Loustalot et al, 2020Medrano-González et al, 1995;Urbán R. et al, 2000Urbán R. et al, , 2017. However, there are still considerable gaps in our knowledge (Hill et al, 2020;Lammers et al, 2023).…”
Section: Distributions Of the Mexican And Central American Wintering ...mentioning
confidence: 99%
“…However, recent genetic and photo-identification analyses have suggested that its range extends into southern, and possibly central, Mexico (Martien et al, 2021;Martinez-Loustalot et al, 2020Taylor et al, 2021). Significant mitochondrial DNA (mtDNA) genetic differentiation was observed when comparing whales from the southern Mexico states of Guerrero (GRO) and Oaxaca (OAX) to BB and BC (in northern Mexico), but not when comparing to whales sampled off Central America (CEA) (Martínez-Loustalot et al, 2020). Photo-identification analysis showed rates of movement were high between Nicaragua and GRO/OAX, intermediate between BB, the central Mexico state of Colima (COL), and GRO/OAX, but low between RA and all other areas (Martínez-Loustalot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations